Developing soybean-based adhesives for heat-treated plywood - Chen, Yizhou (Kansas State University, 2021)
Heat treatment on wood in the absence of oxygen is commonly practiced in industry to improve raw wood properties. However, heat treatment is not widely applied to engineered wood such as plywood because most synthetic adhesives such as urea formaldehyde (UF) adhesives fail in high temperature. In addition, synthetic adhesives, upon heat treatment, would release toxic substances to pollute the environment. In this study, inspired by the high-temperature, controlled, (non-)oxygen condition used in baking, we explored the idea of using plant-protein-based adhesives for heat-treated plywood. Soybean protein (SP) is a proven material for making biobased adhesives for plywood; however, soy flour (SF) is a more affordable candidate. In this study, soy flour was used as the base material for wood adhesives and further modified and formulated with low-value lignin to improve adhesion properties and reduce cost. Glucose was then added in the formula to reveal the effect of the Maillard reaction. Yellow pine plywood samples were prepared and heat treated at different temperatures (190-200 °C) for varied times from 1 to 4 h. The key results were that heat treatment improved the wet adhesion strength of plywood made with SF-based adhesives. Even with unmodified, SF-only adhesives, plywood exhibited robust adhesion and strong water resistance after heat treatment. For example, after 200 °C treatment for 2 h, the wet strength of SF plywood improved from 0 MPa to 1.28 MPa, while plywood made with UF adhesives became delaminated after heat treatment. A content ratio of 50% was the most lignin that can be added into the formula, and it achieved a wet strength of 1.31 MPa. Lignin25%-SF75% was the most practical application, achieving a wet stregnth of 1.43 MPa after heat treatment. Changing the pH of the lignin-SF slurry changed the adhesion of plywood. At a higher pH, more lignin content can be added to the adhesive formula. Heat-treated plywood prepared using soy flour and glucose (SFG) adhesives exhibited a better water resistance of 1.51MPa. The treatment temperature range overlapped with that of the Maillard reaction. The Maillard reaction forms crosslink structures and plays an important role in the water resistance of heat-treated soybean adhesives. It was proposed that hydrophilic functional group loss, protein denaturation, and crosslinking after denaturation helped heat treatment to improve wet adhesion. This study points to new applications of protein-based adhesives and ways to improve plywood properties at a considerably lower cost.
Keywords: Heat treatment; Plywood; Soybean-based adhesive; Lignin; Glucose